Protective effect of low-dose lactulose in dextran sulfate sodium induced ulcerative colitis model of rats - Min Cui; Wei-Ming Yang; Ping Yao (Scientific Reports)
Abstract Although low-dose lactulose has shown a good theoretical foundation for the treatment of ulcerative colitis (UC) in previous studies, the exact effects and mechanism remain unclear. The rats were randomly distributed into 5 groups, i.e., normal drinking water was provided for an initial 14 days in blank control group, 4% dextran sulfate sodium was used for modeling in the remaining 4 groups. During the 15-24th day, rats in the blank control group were administered with 0.9% saline (0.5 ml/d) by gavage. In the rest 4 groups, rats were administered 0.9% saline (0.5 ml/d, UC model), mesalazine (400 mg/kg/d), lactulose (1000 mg/kg/d), and lactulose + mesalazine (two-drug combination) by gavage. In addition to symptoms and pathological changes, serum IL-6, TNF-α, and High-sensitivity C-reactive protein(Hs-CRP) by ELISA analysis, mRNA and protein expression levels of TLR-2, TLR-4, Nuclear factor-κB(NF-κB), IL-6, and TNF-α in colon tissues by RT-qPCR and WB analyses respectively. Meanwhile, short-chain fatty acid(SCFAs) and intestinal flora were analyzed. Low-dose lactulose improved symptoms (diarrhea, blood in stool, weight loss) and pathological inflammation. In addition to serum IL-6, TNF-α, and Hs-CRP, the mRNA and protein expression levels of TLR-2, TLR-4, NF-κB, IL-6 and TNF-α in the colon were down-regulated with the intervention of lactulose.Meanwhile, lactulose decreased the ileocecal PH, increased SCFAs and altered the intestinal flora. Low-dose lactulose may be beneficial to UC by regulating TLRs/NF-κB pathway, reducing ileocecal PH, increasing SCFAs, regulating intestinal flora and improving the intestinal mucosal barrier. Meanwhile, low-dose lactulose and mesalazine may have additive effects upon combination.